P254 Barriers to sexual assault disclosure within sexual health services: a mixed method/population study. (14th July 2019) - Meyrick, Jane; Mccartan, Kieran; Thomas, Zoe; Kowalska, Aga
Abstract : Background: Internationally, the UN reports that an estimated 1 in 3 women experience physical/sexual violence during their lifetime. These rates vary across cultures, age, gender and sexual identity. However, what does not vary is that the majority (UK, 83%) will not report this. It is likely that many will attend mainstream sexual health services for crisis STI screening or emergency contraception. It is clear that a range of psychological and health impacts may be suffered by this group including triple the risk of depression and half survivors not attending cervical screening programmes. Getting the correct help earlier is likely to reduce psychological/physical harm but there is no little or no research around victims interaction with both specialist but importantly mainstream sexual health services. Methods: A population in which sexual assault is high (students) were anonymously surveyed to establish rates of sexual assault/harassment. Participants were asked about reporting behaviour in relation to attendance at SH services. Follow up qualitative interviews examined barriers to services. Qualitative data from a parallel study of actual and potential users of a specialist sexual assault service (Sexual Assault Referral Centre) in which attempts were made to recruit from multiply vulnerable populations at high risk of sexual violence (through support projects around homelessness, drug use, sex workers etc.) were examined for information around barriers to services and disclosure rates. Results: The data around rates of self-reporting victim/survivors attending mainstream sexual health services but not disclosing that assault will be presented and examined for patterns. Analysis of qualitative interview data will be presented in order to establish why rates are low and what might improve reporting. Conclusion: What does a mainstream SH service need to do to in order to show victims of sexual assault that disclosure will be supported and further help is available. Disclosure: No significant relationships.